PENGARUH PENERAPAN PBL TERHADAP HASIL BELAJAR SISWA KELAS X IPS SMAN 1 SUNGAI RAYA - Kristianus, Fransiskus; Margiati, K.Y.; Sugiarto, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to find out the influence of PBL implementation in geography learning toward the student’s result of X IPS SMAN 1 Sungai Raya .The research’s method that has been used is Quasi Experimental Design and it is belong to quantitative research. Population of this research is all of students in X IPS and the sample is X IPS 2 as experiment class and also X IPS 3 as control class. Data collectingon technique used measurement technique and the tool of data collecting was written text in objective multiple choices form. The result had stated that the average score of final test in the experiment class was 78.04 and the average score in the control class was 70. The T-test examination’s result got t_count 3.02 > t_tables 1.67. Thus, the Ha was accepted. It can be concluded that there is influence in the PBL implementation toward the learning outcome of students in X IPS SMAN Sungai Raya. The counting of effect size gets 0.86 with the high category. Based on the counting, it can be proven that the implementation of PBL gives influence to the learning outcome of student X IPS SMAN Sungai Raya.Keywords: Influence, PBL, Learning Outcomes.